Current trends on microextraction by packed sorbent – fundamentals, application fields, innovative improvements and future applications - Pereira, Jorge A. M. (2021)
MEPS, the acronym of microextraction by packed sorbent, is a simple, fast and user- and environmen tally-friendly miniaturization of the popular solid-phase extraction technique (SPE). In fact, it has been widely shown that MEPS can easily replace SPE for most, if not all, previous applications. It can attain this with obvious gains in sample and solvent usage, which is greatly reduced without compromising the extraction efficiency. Furthermore, MEPS can be operated with semiautomatic electronic syringes, making it very reliable and versatile, particularly to handle very low and very high sample volumes. This review will focus on the strengths and weaknesses of this technique and the different MEPS architectures commer cially available in the context of the MEPS applications reported in the last five years. Additionally, innova tive improvements will be highlighted, particularly those related with new applications and recent MEPS configurations and sorbents, such as the controlled directional flow or the innovative µSPEed variant.